Remittances as diplomatic leverage?: The precedent for Trump's threat to restrict remittances to Mexico. (May 2017) - Germano, Roy
As a presidential candidate, Donald J. Trump argued that he could compel Mexico to pay for a border wall by threatening to restrict the flow of remittances sent by Mexicans living in the United States. The proposal was largely dismissed by the press and the political establishment. American officials, however, have used threats to restrict remittances as leverage before. Some experts believe, in fact, that a threat from three House Republicans to restrict remittance flows to El Salvador changed the outcome of El Salvador's 2004 presidential election in favor of the pro-trade, US-friendly candidate favored by the Bush administration. The objectives of this article are to demonstrate that Trump's proposal to use remittances as leverage has precedent and to use survey data to attempt to evaluate the claim that a threat to restrict remittances influenced the outcome of the 2004 Salvadoran presidential election. Statistical tests suggest that remittance recipients were indeed more likely to vote for the Bush administration's preferred candidate in the 2004 election; however, it does not appear that remittance recipients changed the outcome, nor is it clear from the available data whether the remittances threat or some other factor caused remittance recipients to vote differently than non-recipients.